Design and performance analysis of medium access control protocols for QOS in Wimax - Lu, Jin Chang (2010)
This dissertation investigates QoS MAC protocol, architecture and QoS mechanisms. Scheduling algorithms, Adaptive Power Control (APC), Connection Admission Control (CAC) and mapping scheme are proposed to provide QoS provisioning to real-time and non-real-time applications. The main part of the thesis presents four main contributions. • Firstly, the thesis presents a three-tier framework and scheduling scheme to provide QoS in the WiMAX WirelessMAN-SC (Single Carrier) point-to-multipoint (PMP) system. The hierarchical scheduling algorithms perform inter-SS (Subscriber Station), inter-connections and intra-connection packet scheduling to improve QoS for PS (Polling Service) service class while achieving a high Best Effort (BE) throughput. • Secondly, a cross-layer MAC protocol and QoS support framework associated with a two-stage opportunistic scheduling scheme and an adaptive power control scheme are proposed in WiMAX WirelessMAN-SC PMP systems.